The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3934/dcdsb.2008.10.295
|View full text |Cite
|
Sign up to set email alerts
|

One dimensional invariant manifolds of Gevrey type in real-analytic maps

Abstract: Abstract. In this paper we study the basic questions of existence, uniqueness, differentiability, analyticity and computability of the one dimensional center manifold of a parabolic-hyperbolic fixed point of a real-analytic map. We use the parameterization method, reducing the dynamics on the center manifold to a polynomial. We prove that the asymptotic expansions of the center manifold are of Gevrey type. Moreover, under suitable hypothesis, we also prove that the asymptotic expansions correspond to a real-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In contrast to the hyperbolic fixed or periodic points for which the invariant manifolds W u,s are analytic (in fact, they are entire because F is entire) present manifold is only Gevrey 1. This agrees with the theoretical expectations (see [5]). It is immediate to obtain a 2 = 3/4, and it has been observed that a n > 0 (resp.…”
Section: Application To the Hénon Mapsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast to the hyperbolic fixed or periodic points for which the invariant manifolds W u,s are analytic (in fact, they are entire because F is entire) present manifold is only Gevrey 1. This agrees with the theoretical expectations (see [5]). It is immediate to obtain a 2 = 3/4, and it has been observed that a n > 0 (resp.…”
Section: Application To the Hénon Mapsupporting
confidence: 93%
“…Concerning the outer splitting of the 1:3 resonance we note that it cannot be studied by normal form analysis around the elliptic fixed point. It remains finite when crossing the 1:3 resonance as is shown in figure 18 for the Hénon map (5). In this formulation of the Hénon map the elliptic-hyperbolic bifurcation (saddle-center) takes place at c = c 3 = √ 2 and the 3-periodic parabolic orbit on the symmetry axis y = −x has x = 1/ √ 2.…”
Section: Inner and Outer Splitting For Low Order Resonancesmentioning
confidence: 82%
See 3 more Smart Citations